IMMU-35. TREM2 RESTRAINS ANTI-TUMOR CELL ACTIVITY OF MYELOID CELLS IN GLIOBLASTOMA. (14th November 2022) - Sun, Rui; Khan, Saad; Luo, Jingqin; McCornack, Colin; Chen, Yun; Jiang, Haowu; Mao, Diane D; Yang, Alicia; Liu, Qin; Petti, Allegra; Holtzman, David; Kim, Albert
Abstract: Tumor-associated myeloid cell populations occupy a major part of the glioblastoma (GBM) tumor microenvironment (TME). The prevailing view is that myeloid cells in the TME are immunosuppressive and promote GBM tumor progression. However, myeloid cells have the functional plasticity to either restrict or support tumor cell growth. TREM2 has been shown to alter the myeloid cell landscape in cancers arising in the body and plays important roles in brain microglial function in neurodegenerative diseases. But the role of TREM2 in the GBM TME and specifically in myeloid cell function has not been examined. Here we found that TREM2 is highly expressed in myeloid subsets, including macrophages and microglia in human and mouse GBM tumors, and that high TREM2 expression is associated with poor prognosis in GBM patients. TREM2 loss of function in human macrophages and mouse myeloid cells increased tumoricidal capacity in vitro using patient-derived glioblastoma stem cells and mouse glioblastoma cells. Accordingly, we found TREM2 in myeloid cells restricts proinflammatory polarization in both LPS-induced innate and IFNγ-induced adaptive immunity in vitro, mainly through the inhibition of NFκB and MAPK p38 signaling pathways. Orthotopic injection of mouse glioblastoma cells into TREM2 knockout mice increased animal survival compared to littermate wildtype mice. In addition, co-implantation of TREM2 knockdown macrophages or microglia with mouse glioblastoma cells in brains of immunocompetent mice increased animal survival compared to co-implantation of control myeloid cells or injection of tumor cells alone, suggesting an important role for TREM2 in myeloid cells in GBM growth in vivo . Together, these data indicate that TREM2 operates by restricting the anti-tumor and proinflammatory function of myeloid cells in GBM and that inhibition of the TREM2 pathway may represent a potential therapeutic strategy for these patients.